Bimbingan dan Pendampingan Orangtua dalam Proses Pembelajaran Jarak Jauh bagi Siswa MI pada Masa Pandemi Covid-19 - Noor Khasanah; Nur Arifin; Sri Listianah; Noor Malihah (Program Studi BKPI IAIN Salatiga, 2021)
The purpose of this study is to describe the process of parental guidance and assistance for the Islamic Elementary School (Madrasah Ibtidaiyah or MI) students during the covid-19 pandemic and the benefits of parental guidance and assistance while learning at home. This research is descriptive qualitative in nature. The data were collected through observation, interview and documentation. The results of this study indicate that: 1) parental guidance and assistance is needed in online learning which is carried out by utilizing technology using networks because it is carried out online from their respective homes. Parents (family) are the first place where children get education. In connection with distance learning, the task of people increases as a substitute for teachers at home to provide online guidance, supervision, and direction for student learning. The success of children's education cannot be separated from the role of parents as the first teachers to introduce education. 2) parental guidance and assistance for students in online learning has a positive impact for both the parents themselves and the students. Parents become more aware of students' learning progress directly, become more patient, and also gain knowledge because they can learn together with their children. For students, they know more about their responsibilities as students, namely learning, completing assignments from the teachers and being more active in learning.